Formación de líderes académicos en la educación superior. La importancia del contexto para el desarrollo eficaz del liderazgo (Revista Electrónica Calidad en la Educación Superior, 2023)
Amidst the changing nature of higher education, one may wonder how leaders of higher education institutions [HEIs] can succeed and thrive in today’s highly uncertain environments. This qualitative case study examined the factors, practices, and competencies that contributed to effective leadership development of academic leaders at one Canadian university. Through the document analysis and qualitative interviews with academic leaders, it explored the organizational context and individual strategies and competencies that supported leaders in their roles in higher education [HE]. The analysis showed the significance of context as a crucial factor in the effectiveness of leadership development. The findings support further work on developing a different approach to leadership development for academia; one that is founded on an understanding of what academic leaders and their institutions require to succeed and flourish during this time of unprecedented change.
Keywords: academic leaders; leadership development; higher education; Canada